Patient satisfaction with nursing care in an emergency service - Patrícia Fátima Levandovski; Maria Alice Dias da Silva Lima; Aline Marques Acosta (Universidad de Antioquia, 2015)
Objective.To analyze patient satisfaction with nursing care received at a hospital emergency service. Methodology. This is a quantitative, descriptive, cross-sectional study. The sample was composed by 250 patients over 18 years old who used an emergency service in the south region of Brazil. Data were collected using an identification form and the Patient Satisfaction Instrument. Results. Results point to a good level of satisfaction of patients with the nursing care received, with the greatest mean found in the technical-professional care domain. Satisfaction was significantly associated with the room where the patient was and correlated to age, education and the length of stay in the service. Conclusion. It was concluded that patients have good level of satisfaction with the care provided by nurses in emergency service.